African peasants on the move: turmoil between global dynamics, migration and food insecurity - Larcher Carvalho, A.; Schiefer, U.; Dünnwald, S. (Cadernos de Estudos Africanos, 2015)
This issue presents some of the publications resulting from the research project “African societies facing global dynamics: Turbulences between external intervention, migration, and food insecurity” [Dynamics]1. The underlying idea was to investigate contemporary global dynamics faced by African societies, how they interact with internal processes of change and these societies’ responses to these pressures. The contributions address the key issues raised in the Dynamics research project in different ways. They focus on an analysis of migration (internal as well as international), agricultural transformation and food (in)security in different societies and locations. They also explore the links between them and their interrelations with global dynamics. The work was based on case studies conducted in Guinea-Bissau, São Tomé and Príncipe (STP), Cape Verde and Senegal. An additional contribution from Mozambique was also included as it addressed the central issues of the project. Although this research project in itself can only address a few aspects of this complex set of interactions and highlight some of the key issues at play in specific case studies, the project is part of a long-term investigation about the dynamics of change in African agrarian societies which contemplates a wider range of issues.